Solid State Fermentation Research and Industrial Applications - Steudler, Susanne; Werner, Anett; Cheng, Jay J. (Advances in Biochemical Engineering/Biotechnology, 2019)
This book reviews the wide range of products and applications of solid state fermentation as well as the development of this cultivation technology over the last years. In this book, readers will also learn about the challenges of solid state fermentation, including process management, reactor design, scale-up and the formation of process-specific products. Solid fermentation is a traditional cultivation technique of food technology and involves all cultivations of microorganisms on a solid substrate without free liquid phase. In the course of development of Biotechnology it was replaced by liquid cultivation mainly in the western countries. Over the past few years, solid-state fermentation is now becoming more important and has moved more back into focus. Especially, it is suitable for the cultivation of filamentous organisms, like ascomycetes and basidiomycetes, but also for various yeasts and bacteria. The products and applications of solid-state fermentation are as diverse as the microorganisms. They range from enzyme production to the production of antibiotics and pigments to the use in environmental technology and energy production.